The Effect of Taxes, Foreign Ownership, and Company Size on Transfer Pricing - Yusuf, Yusuf; Aziz, M. Wahyu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Transfer pricing is a decision regarding pricing of goods and services transactions to companies that have a special relationship in accordance with the principle of fairness. This study aims to analyze the effect of tax, foreign ownership and company size on transfer pricing in various industry sector companies listed on the Indonesia Stock Exchange for the period 2016 to 2018. The sample selection in this study was carried out using the purposive sampling method and 45 samples were obtained company. The data used is data from the financial statements of the sample companies which are published through the website www.idx.co.id and the official website of each company. The research method used is a quantitative method. The method used is multiple linear regression. Before using regression analysis of regression analysis, the classic assumption test is first performed which includes the normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. Testing in this study was carried out using SPSS software version 25 for windows. The results of this study indicate that tax and foreign ownership have no effect on transfer pricing, while company size has an effect on transfer pricing.